Refiguring prose style: possibilities for writing pedagogy - Johnson, T. R., editor; Pace, Tom, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
This collection takes up a comprehensive study of stylistics in the teaching of writing in higher education. Part I explores the recent history of composition studies, the ways it has figured and all but effaced the whole question of prose style. Part II takes to heart Elbow's suggestion that composition and literature, particularly as conceptualized in the context of creative writing courses, have something to learn from each other. Part III sketches practical classroom procedures for heightening students' abilities to engage style, and part IV explores new theoretical frameworks for defining.
Style and the renaissance of composition studies / Tom Pace -- Where is style going? Where has it been? / Elizabeth Weiser -- Contextual stylistics: breaking down the binaries in sentence-level pedagogy / Rebecca Moore Howard -- Style redux / Kathryn Flannery -- The uses of literature / Tina Kelleher -- Persuasion, more than argument: moving toward a literary sensitivity in the classroom / Allison Alsup -- An arts-centric composition classroom / Gabriel Gomez -- Playing with echo: strategies for teaching repetition in the writing classroom / Melissa A. Goldthwaite -- The "Weird Al" style method: playful invention as serious pedagogy / Keith Rhodes -- When their voice is their problem: using imitation to teach the classroom dialect / J. Scott Farrin -- Style: the new grammar in composition studies? / Nicole Amare -- Balancing thought and expression: a short course in style / Lisa Baird -- Rethinking stylistic analysis in the writing class / William J. Carpenter -- Re-placing the sentence: approaching style through genre / Peter Clements -- Tutoring taboo: a reconsideration of style in the writing center / Jesse Kavadlo -- Rhetor-fitting: defining ethics through style / Dion C. Cautrell -- Style as a system: toward a cybernetic model of composition style / Drew Loewe -- Teaching the tropics of inquiry in the composition classroom / M. Todd Harper -- Writing with the ear / T.R. Johnson.
Keywords: English language -- Rhetoric -- Study and teaching; English language -- Style -- Study and teaching; Interdisciplinary approach in education; Report writing -- Study and teaching